Analysis of Basic Laboratory Skills of Science Education Students Using Pictorial-Based Instruments - Rahayu, Dea Santika; Muqtada, Moh. Rikza (Journal of Tropical Chemistry Research and Education, 2023)
Basic laboratory skills are an important part of science learning, where students are required to work with apparatus, chemicals, procedures, and safety rules. In practice, assessing these skills through direct observation is not always easy because it requires extra time, careful monitoring, and consistent assessment. This study aimed to describe science education students’ basic laboratory skills using a pictorial instrument. The instrument was designed to present laboratory activities in visual form that could be identified before or during laboratory learning. Descriptive research is used with involving 36 science education students. Data were collected using a pictorial instrument consisting three aspects of chemistry laboratory literacy: identifying laboratory apparatus and their functions, describing chemicals and their properties, and explaining laboratory safety procedures on preparing standard solutions from solid samples, preparing standard solutions from concentrated solutions, and conducting acid-base titration. The results showed that students’ ability to identify laboratory apparatus and explain their functions was still generally low, with 53% of students placed in the low category. Students’ ability to describe chemicals and their properties showed a similar pattern, with 69% of students also categorized as low. These findings suggest that many students still have difficulty connecting visual representations of laboratory activities with the conceptual and procedural knowledge needed in chemistry laboratory work. Therefore, pictorial instruments can be used as an initial diagnostic tool to map students’ laboratory readiness and to support the design of more targeted pre-laboratory instruction.